ABCB1 and ABCB19 auxin transporters have synergistic effects on early and late Arabidopsis anther development. Issue 12 (16th March 2015) - Cecchetti, Valentina; Brunetti, Patrizia; Napoli, Nadia; Fattorini, Laura; Altamura, Maria Maddalena; Costantino, Paolo; Cardarelli, Maura
Abstract: Arabidopsis abcb1 abcb19 double mutants defective in the auxin transporters ABCB1/PGP1 and ABCB19/PGP19 are altered in stamen elongation, anther dehiscence and pollen maturation. To assess the contribution of these transporters to stamen development we performed phenotypic, histological analyses, and in situ hybridizations on abcb1 and abcb19 single mutant flowers. We found that pollen maturation and anther dehiscence are precocious in the abcb1 but not in the abcb19 mutant. Accordingly, endothecium lignification is altered only in abcb1 anthers. Both abcb1 and abcb1 abcb19 stamens also show altered early development, with asynchronous anther locules and a multilayer tapetum. DAPI staining showed that the timing of meiosis is asynchronous in abcb1 abcb19 anther locules, while only a small percentage of pollen grains are non‐viable according to Alexander's staining. In agreement, TAM (TARDY ASYNCHRONOUS MEIOSIS), as well as BAM2 (BARELY ANY MERISTEM)—involved in tapetal cell development—are overexpressed in abcb1 abcb19 young flower buds. Correspondingly, ABCB1 and ABCB19 mRNA localization supports the observed phenotypes of abcb1 and abcb1 abcb19 mutant anthers. In conclusion, we provide evidence that auxin transport plays a significant role both in early and late stamen development: ABCB1 plays a major role during anther development, while ABCB19 has a synergistic role. Abstract : Proper development of the male reproductive organ (stamen) is necessary for plant fertility, and is controlled by auxin. We show that the transport of auxin by the ABCB1 and ABC19 proteins is required throughout stamen development for pollen maturation and the timely release of pollen grains in Arabidopsis thaliana .